Compound porcine cerebroside and ganglioside injection attenuates cerebral ischemia–reperfusion injury in rats by targeting multiple cellular processes - Wang M (Dove Medical Press, 2017)
Mingyang Wang,* Yi Zhang,* Lu Feng, Ji Zheng, Shujie Fan, Junya Liu, Nan Yang, Yanyong Liu, Pingping Zuo Department of Pharmacology, Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, China *These authors contributed equally to this work Background: Compound porcine cerebroside and ganglioside injection (CPCGI) is a neurotrophic drug used clinically to treat certain functional disorders of brain. Despite its extensive usage throughout China, the exact mechanistic targets of CPCGI are unknown. This study was carried out to investigate the protective effect of CPCGI against ischemic neuronal damage in rats with middle cerebral artery occlusion (MCAO) reperfusion injury and to investigate the neuroprotective mechanisms of CPCGI. Materials and methods: Adult male Sprague-Dawley rats were subjected to MCAO surgery for 2 hours followed by reperfusion. The rats were administered CPCGI once a day for 14 days after reperfusion, and behavioral tests were performed 1, 3, 7, and 14 days post MCAO. Hematoxylin–eosin staining was used to measure infarct volume, and immunohistochemical analysis was performed to determine the number of NeuN-positive neurons in the ischemic cortex penumbra. Finally, the relative expression levels of proteins associated with apoptosis (Bcl-2, Bax, and GADD45α), synaptic function (Synaptophysin, SNAP25, Syntaxin, and Complexin-1/2), and mitochondrial function (KIFC2 and UCP3) were determined by Western blot. Results: CPCGI treatment reduced infarct size, decreased neurological deficit scores, and accelerated the recovery of somatosensory function 14 days after MCAO. In addition, CPCGI reduced the loss of NeuN-positive cells in the ischemic cortex penumbra. In the ischemic cortex, CPCGI treatment decreased GADD45α expression, increased the Bcl-2/Bax ratio, augmented Synaptophysin, SNAP25, and Complexin-1/2 expression, and increased the expression of KIFC2 and UCP3 compared with sham rats 14 days after MCAO reperfusion injury. Conclusion: CPCGI displays neuroprotective properties in rats subjected to MCAO injury by inhibiting apoptosis and improving synaptic and mitochondrial function. Keywords: compound porcine cerebroside and ganglioside injection, cerebral ischemia reperfusion, multitarget, neuroprotection